Nkx6 proteins specify one zebrafish primary motoneuron subtype by regulating late islet1 expression - Hutchinson, Sarah A. (2007)
The ability of animals to carry out their normal behavioral repertoires requires exquisitely precise matching between specific motoneuron subtypes and the muscles they innervate. However, the molecular mechanisms that regulate motoneuron subtype specification remain unclear. Here we use individually-identified zebrafish primary motoneurons to describe a novel role for Nkx6 and Islet1 proteins in specification of vertebrate motoneuron subtypes. We show that zebrafish primary motoneurons express two related Nkx6 transcription factors. In the absence of both Nkx6 proteins, the CaP motoneuron subtype develops normally whereas the MiP motoneuron subtype develops a more interneuron-like morphology. In the absence of Nkx6 function MiPs have normal early expression of islet1, which is required for motoneuron formation, however they fail to maintain islet1 expression. Misexpression of islet1 RNA can compensate for loss of Nkx6 function, providing evidence that Islet1 acts downstream of Nkx6. We suggest that Nkx6 proteins regulate MiP development at least in part by maintaining islet1 expression which is required both to promote the MiP subtype and to suppress interneuron development.